DEVELOPMENT OF FRICTION STIR WELDING TOOL FOR HIGH-DENSITY POLY-ETHYLENE (HDPE)–CASE STUDY: FIBERGLASS COMPOSITE MATERIAL - Arief, Dodi Sofyan; Wirjosentono, Basuki; Koto, Jaswar; Dalil , M; Susilawati, Anita (Journal of Applied Engineering Science, 2024)
This study aims to develop an effective Friction Stir Welding (FSW) method for composite material of High-Density Poly-Ethylene (HDPE) Pipes. The development of welding tool, there was the addition of an external heating source on the shoulder and probe/pin to overcome the problem of lack of heat resulting from friction between the tool and the material to be welded. The case study was conducted to join the short fiberglass-HDPE composite with a type of ratio of 30% by weight of short fibre and 70% by weight of HDPE, which optimizing parameters such as rotating speed, welding speed, and preheating temperature. The FSW joining process for short fiberglass-HDPE composite sheets was carried out using a Fanuc Series 21i-M CNC milling machine as the driving tool with rotational speed (ω) varied in 3 conditions, namely 600 rpm, 800 rpm and 1000 rpm, and welding speed (v) or feeding at 5 mm/minutes and 10 mm/minutes. The temperature was controlled according to the liquid point of High-Density Poly-Ethylene, which was 130oC, and raised to 150oC and 170oC. The 12 pieces of thermocouple were used along the track on the material and jig plates at the top, middle and bottom. Then, the results of joining the sheets were made in the form of specimens with sizes according to ASTM 3039. The tensile tests of the specimens were carried out at a rate of 0.01 mm/s. The results showed the highest tensile strength was an average value of 24.52 MPa at a rotational speed of 800 rpm, the feeding of 5 mm/min and the temperature of 130oC. The lowest tensile strength was an average value of 17.54 MPa at a temperature of 170°C with a speed of 600 rpm.